1983
DOI: 10.1152/ajpcell.1983.245.3.c235
|View full text |Cite
|
Sign up to set email alerts
|

Bumetanide inhibits (Na + K + 2Cl) co-transport at a chloride site

Abstract: Chloride-dependent cation transport systems in a number of cells and tissues are inhibited by 5-sulfamoylbenzoic acid loop diuretics, such as furosemide and bumetanide. Interactions between chloride and bumetanide have been examined in the catecholamine-activated (Na + K + 2Cl) co-transport pathway of the duck red blood cell. Levels of chloride were varied while maintaining a constant ratio of internal to external chloride across the cell membrane. Increasing external chloride from 20 to 100 mM shifted the dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
84
2

Year Published

1985
1985
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(97 citation statements)
references
References 21 publications
11
84
2
Order By: Relevance
“…To determine whether concurrent fluid secretion is necessary to transport mucus into the luminal perfusate (26, 27), we added bumetanide (10 -4 M) to HCO 3 --containing serosal solutions to selectively block the Na-K-2Cl cotransporter (NKCC) and inhibit fluid secretion (28). We found that the amount of mucus released into the perfusate was significantly decreased in both PGE 2 - and 5-HT-stimulated conditions ( Figure 4, A-D).…”
Section: Figurementioning
confidence: 99%
“…To determine whether concurrent fluid secretion is necessary to transport mucus into the luminal perfusate (26, 27), we added bumetanide (10 -4 M) to HCO 3 --containing serosal solutions to selectively block the Na-K-2Cl cotransporter (NKCC) and inhibit fluid secretion (28). We found that the amount of mucus released into the perfusate was significantly decreased in both PGE 2 - and 5-HT-stimulated conditions ( Figure 4, A-D).…”
Section: Figurementioning
confidence: 99%
“…The dose of bumetanide which resulted in 50% inhibition of 86Rb+ uptake was 2 X 10-6 M, as compared with 7 X 10-6 M for inhibition of VIP-induced I,,. The discrepancy may be explained by the large experimental error in the Ussing chamber experiments and by changes in the affinity of bumetanide for the cotransporter by temperature or small differences in Na', K+, or Clconcentrations for the two experimental conditions (37,38).…”
Section: Resultsmentioning
confidence: 99%
“…The results also suggest that this transport pathway serves as the Cl-uptake step in the CF-secretory process, and is required to sustain the action ofprostaglandin El. Na',K+,Clcotransport has been observed in a variety of cells and is inhibitable by bumetanide (30)(31)(32)(33)(34)(35)(36)(37). In a recent study, the existence of a bumetanide-sensitive Na',K+,Cl-cotransport pathway has been demonstrated in the T84 cells and localized to the basolateral membrane (10).…”
Section: Discussionmentioning
confidence: 99%